2022
DOI: 10.3390/ijerph19116694
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in South Africa: Lessons for Future Pandemics

Abstract: Vaccine hesitancy, long considered a global health threat, poses a major barrier to effective roll-out of COVID-19 vaccination. With less than half (45%) of adult South Africans currently fully vaccinated, we identified factors affecting non-uptake of vaccination and vaccine hesitancy in order to identify key groups to be targeted when embarking upon COVID-19 vaccine promotion campaigns. A cross-sectional, anonymous online survey was undertaken among the South African adult population in September 2021. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 32 publications
10
33
0
Order By: Relevance
“… Logistic regression Correa-Rodriguez 43 2022 Spain. Patients with systemic autoimmune disease 319 , F 92% , Age 31–50 Cross-sectional study May-June 2021 HLVa Scale Functional 2.59 ± 0.74; Interactive-critical 3.07 ± 0.60 Area of residence, civil status and socio-economic status; Attitudes perceptions and beliefs about COVID-19 vaccines - Intention to be vaccinated In 96.7% of patients Mann-Whitney, Kruskal Wallis, Fisher’s Costantini 44 2021 Japan, Family carers 292, F 44%, Age 53 ± 9.1 Cross-sectional survey through an online research service company, May–June 2021 Nine HL items and nine focused on COVID-19 vaccines Mean scores across the nine items range: VL from 2.55 to 2.84 HL from 2.69 to 2.94 Nine questions administered Hours of care provided, having children, income, marital status Patterns of VL relative to HL - VL lower in older participants Student’s t-test, chi-square, single-variable and multivariable regressions Durmus 36 2021 Turkey , General population 596 , F 60.6% , Age 32.53 ± 14.96 Cross-sectional online survey Early 2021 COVID-19 VLS (defined as HLVa) Functional: 2.40 ± 0.75 Inter-critical: 2.60 ± 0.69 - VL scale Construct validation in Turkish - Two dimensions of the scale Exploratory (EFA) and Confirmatory Factor Analysis (CFA) Engelbrecht 45 2022 Engelbrecht 46 2022 ...…”
Section: Resultsmentioning
confidence: 99%
“… Logistic regression Correa-Rodriguez 43 2022 Spain. Patients with systemic autoimmune disease 319 , F 92% , Age 31–50 Cross-sectional study May-June 2021 HLVa Scale Functional 2.59 ± 0.74; Interactive-critical 3.07 ± 0.60 Area of residence, civil status and socio-economic status; Attitudes perceptions and beliefs about COVID-19 vaccines - Intention to be vaccinated In 96.7% of patients Mann-Whitney, Kruskal Wallis, Fisher’s Costantini 44 2021 Japan, Family carers 292, F 44%, Age 53 ± 9.1 Cross-sectional survey through an online research service company, May–June 2021 Nine HL items and nine focused on COVID-19 vaccines Mean scores across the nine items range: VL from 2.55 to 2.84 HL from 2.69 to 2.94 Nine questions administered Hours of care provided, having children, income, marital status Patterns of VL relative to HL - VL lower in older participants Student’s t-test, chi-square, single-variable and multivariable regressions Durmus 36 2021 Turkey , General population 596 , F 60.6% , Age 32.53 ± 14.96 Cross-sectional online survey Early 2021 COVID-19 VLS (defined as HLVa) Functional: 2.40 ± 0.75 Inter-critical: 2.60 ± 0.69 - VL scale Construct validation in Turkish - Two dimensions of the scale Exploratory (EFA) and Confirmatory Factor Analysis (CFA) Engelbrecht 45 2022 Engelbrecht 46 2022 ...…”
Section: Resultsmentioning
confidence: 99%
“…However, inequities in access to immunization within nations continue, and there remain difficulties in achieving goal vaccination rates ( 49 ). LMICs accounted for less than 40% of the studies we included ( 22 , 28 , 29 , 32 , 33 , 35 , 37 , 39 ), more research in LMICs is required due to the importance of VL in vaccination. To prepare for the future’s unpredictability, countries could develop plans to increase vaccination rates and improve the public’s VL.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies have examined the relationship between adult VL and COVID-19 vaccination results (20,22,(31)(32)(33)(34)(35). Of these, only one study conducted in Bangladesh found no association between vaccination literacy and intention to receive the COVID-19 vaccine, in contrast to the other 6 studies (32).…”
Section: Adults' Vl and Vaccinationmentioning
confidence: 99%
“…One of the contributing factors to a lack of trust stems from the findings of South African investigators who flagged COVID-19 contracts for possible corruption and fraud. 12 Similar findings from a study conducted by our group in February 2020 - March 2021 indicated that a growing number of persons have become hesitant about vaccines, fearing side effects and not appreciative of the enormous health and economic benefits that vaccines provide. 13 Unfortunately, the fast-tracking of the clinical development of vaccine candidates for COVID-19 has added another reason for vaccine hesitancy, even among those who might otherwise be very confident in vaccine safety and efficacy such as healthcare workers as shown by another study conducted by our group in March – May 2021.…”
Section: Findings and Discussionmentioning
confidence: 54%
“… 14 Even whilst vaccines were still in developmental stages, the fear of potential side effects was noted as the fundamental reason for the lack of intent to get vaccinated, purporting that risk perception is a key barrier to COVID-19 vaccine uptake. 12 …”
Section: Findings and Discussionmentioning
confidence: 99%